2022
DOI: 10.3390/w14060992
|View full text |Cite
|
Sign up to set email alerts
|

Flood Risk Perception and Its Attributes among Rural Households under Developing Country Conditions: The Case of Pakistan

Abstract: Managing and communicating flood risks necessitates a strong understanding of how people perceive risk. It has become critical to examine risk perception to implement effective disaster risk management (DRM) measures. Socioeconomic determinants have an impact on risk perception, which in turn affects future adaptive capacity and disaster preparedness. First and foremost, this research attempts to determine how Pakistani people in rural areas perceive flood risk, and second, to examine the factors that can infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 62 publications
1
9
0
Order By: Relevance
“…The differences within countries, and the variability in the gaps between the countries, in the risk perceptions of the general population, compared to first responders, support previous studies which claimed that first responders, as a specific professional group, differ from the general public regarding specific demographic characteristics (Brown et al, 2021;Kollmann et al, 2022;Shah et al, 2022) or personality traits (Al-Dahash et al, 2022). The contribution of the discussion made in this study is in connecting these gaps with additional possible explanations, such as different policies in the various countries, the relative focus given for each type of emergency, and the frequency of events.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The differences within countries, and the variability in the gaps between the countries, in the risk perceptions of the general population, compared to first responders, support previous studies which claimed that first responders, as a specific professional group, differ from the general public regarding specific demographic characteristics (Brown et al, 2021;Kollmann et al, 2022;Shah et al, 2022) or personality traits (Al-Dahash et al, 2022). The contribution of the discussion made in this study is in connecting these gaps with additional possible explanations, such as different policies in the various countries, the relative focus given for each type of emergency, and the frequency of events.…”
Section: Discussionsupporting
confidence: 80%
“…Different risk perceptions may stem from varied factors including demographic characteristics (such as age, gender, and socio-economic status) ( Brown et al, 2021 ; Kollmann et al, 2022 ; Shah et al, 2022 ); personality traits (such as ways of coping with stressful situations, views concerning fate versus control of events; leadership qualities) ( Al-Dahash et al, 2022 ); cultural and social contexts (for example, local values and norms, or trust in data and in the authorities) ( Renn and Rohrmann, 2000 ; Cori et al, 2022 ); assorted beliefs (such as religion, level of religiosity, fears, political or other attitudes) ( Grima et al, 2021 ; Siegrist et al, 2021 ); as well as familiarity or knowledge about the hazard ( Al-Dahash et al, 2022 ). The Social Amplification of Risk Framework (SARF) suggests that the interaction between psychological, cultural, social, and contextual factors, and the characteristics of the adversities, impact the risk perception and consequently, also influence protective behavior ( Knuth et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we concluded that these factors should not be considered in the ordered logit regression. Other studies also found only insignificant effects of socioeconomic factors, including education, occupation and income, on flood risk perception [62,[65][66][67].…”
Section: Factors Influencing Households' Flood Risk Perceptionmentioning
confidence: 94%
“…However, a higher risk perception when accompanied by a low coping appraisal, can lead people to avoid taking protective actions against the risk, which is referred to as fatalism [31]. Many studies have been conducted in the context of flood perception risk elsewhere in different parts of the world [16,[35][36][37][38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%